Subsequent COVID-19 Prophylaxis in COVID-19 Associated Glomerulopathies - Therese Boyle; Emma O’Lone; Elaine Phua; Janet Anderson; Amanda Mather; Suran L. Fernando (Vaccines, 2023)
Successful vaccination has been the decisive factor in the overall decline of SARS-CoV2 infection related morbidity and mortality. However, global effects of the COVID-19 pandemic are ongoing, with reports of glomerular disease occurring in relation to both infection and vaccination. A particular rise in anti-GBM disease has been identified. Information is still emerging regarding the optimal management of such cases. We reviewed anti-GBM antibody detection rates at our test center over the past 5 years. We followed three patients with biopsy confirmed glomerular disease temporally related to COVID-19 vaccination. Each patient proceeded to receive subsequent COVID-19 vaccination as per immunologist recommendations. Further assessment included COVID-19 antibody testing in each case. A three-fold increase in significant anti-GBM antibody results noted at our center was associated with COVID infection in 10% of cases, and COVID vaccination in 25% of cases. We demonstrated that subsequent vaccination did not appear to lead to adverse effects including relapse in our three cases of COVID-19 vaccine-associated GN. We also identified positive COVID-19 antibody levels in two out of three cases, despite immunosuppression. We report a rise in anti-GBM antibody disease incidence. Our small study suggests that COVID-19 antibody testing can help determine COVID prophylaxis requirements, and subsequent vaccination with an alternative vaccine type appears safe.